Immunoglobulin a vasculitis with testicular/epididymal involvement in children: A retrospective study of a ten-year period - Hu, Jian-Jun; Zhao, Yao-Wang; Wen, Rong; Luo, Yang-Yang; Zhou, Wei-Guo; Liu, Yu-Hang; Qin, Feng; Liu, Chang; He, Tian-Qu (Frontiers in Pediatrics, 2023)
The clinical characteristics and risk factors for testicular/epididymal involvement in 73 children with immunoglobulin A vasculitis (IgAV) who were admitted to our hospital between January 2012 and November 2022 were reviewed. The demographic data, laboratory parameters, and follow-up data of the patients were compared to those of 146 males without testicular/epididymal involvement. A logistic regression analysis was performed to determine the variables associated with testicular/epididymal involvement. The prevalence of testicular/epididymal involvement among male patients with IgAV was 1.3% (73/5,556). Increased blood flow in the testes and/or epididymis on ultrasound was found in 71 patients. The remaining two patients underwent surgical exploration for loss or reduction of testicular blood flow. One patient underwent orchiectomy for intraoperative confirmation of complete right testicular infarction. Pathological findings revealed IgA immune complex deposition in the testis. Patient age (odds ratio [OR] = 0.792; 95% confidence interval [CI]: 0.682–0.919, p = 0.002), platelet count (OR = 1.011; 95% CI: 1.002–1.020, p = 0.013), and immunoglobulin M (IgM) levels (OR = 0.236; 95% CI: 0.091–0.608, p = 0.003) were strongly associated with the occurrence of testicular/epididymal involvement in IgAV. Therefore, young age, increased platelet count, and low IgM levels in patients with IgAV are potential risk factors for testicular/epididymal involvement. Doppler ultrasound can help differentiate IgAV from acute scrotum. Most patients with testicular/epididymal involvement have good prognoses, although serious complications such as testicular infarction may occur.